Methodological Principles of Knowledge of the State and Law - Vladimir Valentinovich Kozhevnikov; Muhammad Ridwan (Polit Journal Scientific Journal of Politics, 2025)
This scientific article is devoted to the problems of methodological principles of knowledge of the state and law. In particular, the question of whether they are elements of the methodology of knowledge of state and legal phenomena is considered. Particular attention is paid to one of these principles, such as objectivity. Examples from domestic legislation that do not correspond to it are demonstrated.